Pédagogies de l’écologie dans les écoles d’architecture et de paysage. D’un mouvement marginal à un enjeu majeur - Dimitri Toubanos (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article proposes a reading of the relation between ecology and pedagogy in French schools of architecture and landscape. It retraces the lengthy path to integrating ecology into schools, while highlighting the impetus generated by teacher networks set up to address these issues in the 2000s. Further, it describes how social, economic and political changes in favor of ecology have influenced architectural studies. Finally, drawing on the activities of the EnsaÉco scientific and educational network, trends in environmental transition education are described, both in terms of content and teaching methods.